Generation Z as a challenge for the traditional corporate culture in Poland - Mazurek, Magdalena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The objective of the paper is to analyze the skills and attitudes of Generation Z in Poland in order to update and systematize data on features of all generations that are active in the Polish labour market. The issue deserves research due to the specific perception of work and business by young people, which, by affecting their motivation, forces companies to modify their operations. Employee engagement programmes must be adjusted to the skills and preferences of individualists, who are proficient in Internet use, but inconsistent in their decisions or endeavors and not prepared for teamwork. Short attention span and short-lived interests of young staff, which require a kinesthetic, multimodal working environment, may disrupt a traditional company culture. Communication with Generation Z, used to ongoing communication and co-creating, is a serious challenge to managers. Low levels of soft skills and economic literacy may undermine the benefits from excellent adaptability of the young generation. Tabular summaries of generation-based characteristics will be presented. The paper is based on the literature on the older generations as well as reports and statistics on Generation Z.